Inspeção visual automática de mamões - Simão, Josemar (2003)
This work shows the development of an automatic inspection system for papaya fruits. This system can measure the size and the degree of maturation of the fruits, and classify them accordingly. The regional sector of papaya production and exportation has grown and the use of an automatic visual inspection system can contribute for the production increase and maintenance of the standards of quality demanded by the consuming markets. The automatic visual inspection systems have often been an alternative to the traditional processes of inspection done by trained individuals. The main reasons are costs reduction and the guarantee of the quality standard assured by the inspection of all fruits in a lot. In contrast, human inspectors get tired with repetitive work and present inconsistency in the inspection criteria. The system basic structure is a conveyor belt carrying a continuous flow of fruits and a digital video camera, located above, which gets a sequence of images of the moving fruits. These images are processed and analyzed by a personal computer. The first processing stage is the conversion of color to binary images for fruits dimensions estimation. The maturation is quantified by a hue histogram curve of the fruits in the color images. Comparing with data in a database, that stores the knowledge of experts, the information acquired can be used to classify the fruits and set up a mechanism capable to separates them as necessary. The results had shown that a set of the simple hardware could evaluate the dimensions and the degree of maturation of the fruits despite illumination changes.